Leveraging Value of Disparate Information Assets XML to the rescue. - Huck, Kevin (XML journal :the ultimate enterprise resource.)
Businesses today are trying to cope with an overabundance of electronic information. Beyond the silos of structured data that have been managed with traditional database technologies is a need to manage the ever-increasing deluge of unstructured data types and sources. E-mails, spreadsheets, office documents, HTML files and so on, contain a wealth of information, but are not easily accessible across the organization.